Predictive multiphase evolution in Al-containing high-entropy alloys - L. J. Santodonato (Nature Portfolio, 2018)
Exploration of high entropy alloy phases where little experimental data exists is still challenging. Here, the authors develop an approach where parameters from first principle simulations are incorporated into Monte Carlo simulations to reproduce phase evolution of aluminium-containing high entropy alloys.